Kite Museum Observation - Kusumaningrum, Anisa Putri; Wardani, Dwita Chika; Azzahra, Talitha Daffa; Andini, Davi Ayu (CV ODIS, 2023)
Kite is a traditional game that has been a popular game among children since time immemorial. Kites originated in China around 2500 years ago, this study has explained how the history of the Kite Museum, the contents of the Kite Museum and the condition of the Kite museum, this study uses qualitative methods, and the results of this study shows the number of Kite collections in this museum numbered 600, but the number continues to grow as the coming collections new from the local and foreign sailors and kites made by themselves by museum employees.